Cost-effective reliable transmission service for Internet of Flying Things - Najmul Hassan; Noor M Khan (International Journal of Distributed Sensor Networks)
High-speed quality Internet provision for aircraft passengers is thought to be one of the major unresolved challenges for ubiquitous Internet provision. This article aims to resolve the problem of airborne Internet access with high quality of service for modern Internet of things devices. Large remote regions in the ocean along the busy air routes (e.g. Atlantic Ocean) require high-speed, reliable, and low-cost airborne Internet (i.e. Internet provision to the aircraft) to manage various delay- and throughput-sensitive applications. Conventional satellite-based solutions can be an alternate for Internet provision in such far-flung areas; but, such solutions are lacking quality of service (with longer delays and low bandwidth) and are significantly costly. Fortunately, the underwater optical fiber cables deployed across the oceans pass along the same busy air routes. This infrastructure of underwater optical fiber cables can be exploited for Internet backbone providing high quality of service for wireless Internet provision to the commercial aircraft. Dedicated stationary ships deployed along these underwater optical fiber cables can be utilized for Internet provision, navigation, and security to ships and aircraft. This article not only proposes the networking infrastructure of the submarine cable-based airborne Internet access architecture but also presents a novel routing scheme for airborne ad hoc networks. Also, we analyze quality of service provision as compared to other existing techniques. Our simulation results show that our proposed solution outperforms other existing schemes for airborne Internet service provision, in the presence of high mobility and dynamic topology changes.